Splicing of the rSlo gene affects the molecular composition and drug response of Ca2+-activated K+ channels in skeletal muscle. - Maria Maddalena Dinardo; Giulia Camerino; Antonietta Mele; Ramon Latorre; Diana Conte Camerino; Domenico Tricarico (PLoS ONE)
The molecular composition and drug responses of calcium-activated K(+) (BK) channels of skeletal muscle are unknown. Patch-clamp experiments combined with transcript scanning of the Kcnma1 gene encoding the alpha subunit of the BK channel were performed in rat slow-twitch soleus (Sol) and fast-twitch flexor digitorum brevis (FDB) skeletal muscles. Five splicing products of the Kcnma1 gene were isolated from Sol and FDB: the e17, e22, +29 aa, Slo27 and Slo0 variants. RT-PCR analysis demonstrated that the expression of e22 and Slo0 were 80-90% higher in FDB than Sol, whereas the expression of Slo27 was 60% higher in Sol than FDB, and the +29 aa variant was equally expressed in both muscle types. No beta 1-4 subunits were detected. In Sol, a large BK current with low Ca(2+) sensitivity was recorded. The BK channel of Sol also showed a reduced response to BK channel openers, such as NS1619, acetazolamide and related drugs. In FDB, a reduced BK current with high Ca(2+) sensitivity and an enhanced drug response was recorded. The total BK RNA content, which was 200% higher in Sol than in FDB, correlated with the BK currents in both muscles. Drug responses primarily correlated with e22 and Slo0 expression levels in FDB and to Slo27 expression in Sol muscle. In conclusion, phenotype-dependent BK channel biophysical and pharmacological properties correlated with the expression levels of the variants in muscles. These findings may be relevant to conditions affecting postural muscles, such as prolonged bed-rest, and to diseases affecting fast-twitch muscles, such as periodic paralysis. Down-regulation or up-regulation of the variants associated with pathological conditions may affect channel composition and drug responses.